Durability of initial antidiabetic monotherapy and subsequent treatment adjustment patterns among newly treated type 2 diabetes patients - Noh Y; Lee S; Shin S (Dove Medical Press, 2018)
Yoojin Noh,1 Sukhyang Lee,1,2 Sooyoung Shin1,2 1Department of Clinical Pharmacy, College of Pharmacy, Ajou University, Yeongtong-gu, Suwon, Republic of Korea; 2Research Institute of Pharmaceutical Science and Technology (RIPST), Ajou University, Yeongtong-gu, Suwon, Republic of Korea Background: As newly available antidiabetic drugs (ADs) are used more commonly as initial hypoglycemic choice for early stage diabetes patients, there is an urgent need to investigate how these agents may differ in treatment durability relative to metformin. This study aimed to investigate the incidence and risk of treatment adjustment among newly treated type 2 diabetes mellitus (T2DM) patients receiving an oral AD as initial monotherapy. Methods: T2DM patients registered in the National Health Insurance Program who were newly prescribed an oral AD were identified. Time to treatment addition or switch to alternative antidiabetic therapy was determined using the Kaplan–Meier survival analysis. Cox proportional hazards regression was performed to estimate the hazard ratio (HR) after adjusting for potential confounding factors. Results: The median time to treatment adjustment was shorter for sulfonylureas (SUs), dipeptidyl peptidase-4 (DPP-4) inhibitors, alpha-glucosidase (AG) inhibitors, and thiazolidinediones (TZDs) compared to that for metformin. Initiation of therapy with SUs or DPP-4 inhibitors was associated with a significantly higher risk of both treatment addition and switching than with metformin (HR 1.49 versus 1.47 for overall treatment adjustment, respectively). In contrast, among incident users of AG inhibitors or TZDs, only the hazard of switch was substantially increased compared to metformin starters (6.19, 95% confidence interval [CI] 5.77–6.64 and 7.31, 95% CI 6.35–8.42, respectively). When addition and switch events were collectively assessed, the risk of treatment adjustment was significantly elevated in all non-metformin cohorts. Conclusion: Our results demonstrated that the durability of metformin as an initial monotherapy was superior to that of other ADs, including newer classes of antidiabetics, and appeared to be more effective in delaying treatment adjustment in real-world clinical practice. Keywords: drug utilization patterns, antidiabetic drugs, type 2 diabetes